Pengembangan Modul Digital Hypercontent Pada Materi Sejarah Perkembangan Bahasa Indonesia Berorientasi HOTS - Sabitul Kirom (Peneliti.net, 2021)
This study aims to develop teaching materials for HOTS-oriented digital hypercontent modules on the history of the development of the Indonesian language. The HOTS-oriented digital hypercontent module has several advantages, namely lectures become more varied and interesting because the content in the module varies, ranging from images, animation, video, audio, to being able to be connected to various online applications/sites. The developed module can be saved in offline or online format. The module is also equipped with materials, discussions, quizzes, and evaluations. This research uses Research and Development (R and D) method with ADDIE development model. The research instruments used include validation sheets and user questionnaires. The data analysis technique was carried out by calculating the results of the validation assessment and user questionnaires. The results showed that the digital module developed was feasible to be used as teaching material. The digital module developed got a score of 88.90% on the material aspect and 90.20% on the media aspect. The criteria used include aspects of appearance, aspects of introduction, aspects of content/material description, and aspects of evaluation. The results of the response test to lecturers and students respectively got a score of 89.15% and 90.22%.